Pemaknaan Distopia dan Ilusi Kebahagiaan dalam Film Don't Worry Darling - Bintang, Muhammad; Saputra, Sepriadi; Astrid, Gita (Jurusan PTIK Universitas Negeri Manado, 2025)
This study discusses the representation of dystopia and the illusion of happiness in the film Don't Worry Darling using Roland Barthes' semiotic analysis. Directed by Olivia Wilde, the film features a fictional community called Victory, which on the surface is depicted as an ideal world, full of order and happiness. However, behind this visualization lies a dystopian reality that restricts individual freedom, especially that of women. This study uses a qualitative approach with audiovisual text analysis techniques. Primary data consists of film scenes relevant to the issues of dystopia, the illusion of happiness, and power relations, while secondary data is obtained from supporting literature. The results of the study show that the visual signs in the film operate on three levels of meaning according to Barthes: denotation, connotation, and myth. At the denotation level, the film depicts harmonious family life and a stable social environment. At the connotation level, these signs carry meanings of repression and gender role restrictions. Meanwhile, at the myth level, the film reinforces patriarchal ideology through a narrative of family happiness that seems natural. The character Alice appears as a representation of resistance against the patriarchal system, attempting to dismantle the illusion of manufactured happiness. The film also shows how visualization and technology function as tools of social control that mask oppression with a facade of comfort. Thus, Don’t Worry Darling not only provides entertainment but also offers criticism of the ideology that manipulates happiness as a means of domination.